Development of the intersectoral care reported by patients survey for primary and oral healthcare - Smits, Kirsten; Zande, Marieke M. van der; Hek, Reanne; Assendelft, Pim W. J. J.; Rozema, Fred R.; Wright, Kenneth R.; Dolce, Maria C.; Riedy, Christine A.; Barrow, Jane R.; Hüttig, Fabian; Listl, Stefan (International journal of integrated care, 2025)
Introduction: Oral and general health are closely related, and many oral and chronic-systemic diseases have the same risk factors. However, in most countries dental and general health care systems are separated. Integration of care for patients with closely related, multiple conditions is therefore important to ensure they receive the best quality of care. We aimed to develop a short and easy-to-understand survey to be used by patients to assess integration of dental and primary health care through their perceptions. Methods: This study used both qualitative and quantitative methods. A modified online Delphi method was used for development of the survey. A panel consisting of seven experts assessed the survey in three rounds. The experts were based in the United States, Germany and the Netherlands and had different professional backgrounds, including general practice and dentistry. The initial framework and set of proposed questions were based on a previous survey with a similar focus. During two discussion rounds and one online round the framework and the questions were assessed and modified by the experts. The survey was then assessed for understandability among 18 patients and thereafter piloted among 199 patients. Results: The final questionnaire derived from the consensus procedure contains thirteen questions which address the following five domains: patients’ wishes, expectations, awareness and concerns regarding communication between health care providers; patients’ perception of health care providers’ knowledge; health care provider-patient communication about health status; utilization of health care; and self-rated health. The consensus procedure also yielded improvements in the understandability of survey items: one survey item was changed from a multiple-choice question into a yes/no question, answer options were added to three other survey items, four survey items were slightly changed in wording, and five items remained unchanged. Conclusion: We developed the short, easy-to-understand Integrated Care Reported by Patients Survey to assess integration of dental and primary health care as perceived by patients. In the future, the developed survey is intended to be tested for validity and translated to other languages. The survey provides opportunities for usage in research and as a tool in quality improvement and feedback systems for health care providers.
Gesehen am 02.02.2026